Implementation of Pedagogical Design in Preparing the Future Teacher for Innovative Activities - Eshpulatov Shakir Nabievich (Genius Publishing Group, 2023)
In this article, we will present the results of a study on the implementation of pedagogical design in preparing a future teacher for innovative activity, the features of the development and implementation of a project in education.
Keywords: analysis; research; planning